THE ROLE OF MINDFULNESS IN ACHIEVING ORGANIZATIONAL EXCELLENCE, FIELD STUDY OF THE SENIOR LEADERSHIP SAMPLE AT KARBALA UNIVERSITY - Zainab Abu Ali Khalaf; Suhair Adel Hamed (Scholar Express Journals, 2022)
The research aims to recognize the role of mindfulness of senior leaders in the research organization and its impact on achieving organizational excellence. The research organization was the University of Karbala in its colleges and the sample was determined in the senior leadership of the university by the heads of departments and associates of deans, deans, and associates of the rector. (85) persons. The main problem in the research organization was the low level of mental alertness of senior leadership In addition to the low level of organizational excellence compared to other universities and the study of the extent to which there is a relationship between the two variables, and for the purpose of understanding the relationship and the effect between the two variables, two main hypotheses were formulated: There is a statistically significant correlation between mindfulness and organizational excellence overall and its dimensions individually. There is a statistically significant effect between mindfulness in general, and organizational excellence in general, and its individual dimensions, and some statistical methods were relied upon to process the data obtained from the questionnaire using the descriptive analytical approach based on the program (Amos v.23, spss v.23). As auxiliary tools in statistical analysis such as the normal distribution test and the analysis of the certainty factor in addition to percentages, arithmetic mean, standard deviation, coefficient of variation, and level of significance, the simple correlation coefficient was relied on to know the correlation between the two variables. As for the effect of the independent variable on the dependent, the simple linear regression coefficient was used to test the validity of the hypotheses The current research reached a set of conclusions, including the existence of a correlation and It was raised between mindfulness and organizational excellence, as well as the organization in question suffers from a decrease in the number of young leaders to occupy leadership positions, in addition to the fact that leaders from the female component were very weak, which led to the size of the role of women in occupying leadership positions. In addition to this, and the existence of a complex hierarchical organizational structure, this was reflected in The slowness of the procedures you are taking. The current research recommended the need to enhance the mental alertness of the senior leadership through the establishment of continuous training workshops and the development of appropriate strategies for this, as well as increasing attention to human resources, which are the basis of organizational excellence, and moving towards adopting organizational structures that are more simplified for procedures to ensure ease of work procedures as well as the adoption of An integrated strategic orientation that ensures the implementation of the appropriate organizational excellence model for the organization in question
Keywords: Mindfulness; Organizational Excellence